(3GdSdhc GdJfXjej aj HjFI GdYhdeI h GdGfJQfJ (B/s - (3Wg, WGQbs ((3GdGScfOQjI(B: s (3GdLGeYI GdLOjOI(B, s, 2007)
(3jJfGhd GdcJGH GSGSjGJ Yde GdSdhc GdJfXjej , GdfXGe GdGLJeGYj h GdKbGaI h GdHjFI GdJfXjejI , Sdhc GdGaQGO h GdLeGgGJ h GdefXeGJ aj HjFI GdYhdeI h GdGfJQfJ, bjGOI GdYGedjf h GdSdhc GdbjGOj , GdfXQjGJ GdeYGUQI h GdeTGQcI h GdeSGfOI , GdOGaYjI h fXe GdecGaCJ h JYOjd GdSdhc GdJfXjej , GdQbGHI Ydi GdGOGA GdJfXjej , JfXje GdGaQGO h GdGfTWI OGNd HjFI GdYed , GdJUejeGJ GdJfXjejI , GOGQI GdJZjjQ GdJfXjej h GdVZhW Ydi GdGaQGO OGNd HjFI GdYed(B.s
Keywords: (3GdSdhc GdEOGQjs